Stochastic Volterra Equations Under Perturbations - Lizama-Yanez, C (University of Washington, 2014)
We study stochastic perturbed Volterra equations of convolution type in an infinite dimensional case. Our interest is directed towards the existence and regularity of stochastic convolutions connected to the equations considered under some kind of perturbations. We use an operator theoretical method for the representation of solutions.